2020
DOI: 10.1002/jmv.26088
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene polymorphisms of CD55 with susceptibility to and severity of hand, foot, and mouth disease caused by enterovirus 71 in the Han Chinese population

Abstract: Hand, foot, and mouth disease (HFMD) caused by enterovirus 71 (EV71) can lead to high morbidity and mortality, and genetic background plays an important role during the disease process. We investigated the association between the single‐nucleotide polymorphism (SNP) rs2564978 of the CD55 gene and susceptibility to and severity of HFMD using the SNPs can multiple SNP typing methods. Soluble CD55 (sCD55) expression was significantly lower in the EV71 HFMD group than in the control group and lower in severe cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Indeed, it appears that a combination of host and viral factors is associated with the likelihood of progressing to severe disease. These factors include polymorphisms within host immune and receptor-associated genes ( 3 5 ). While there is some cross-reactivity among the different genogroups (A, B1 to B5, and C1 to C5) ( 6 ), the antigenic variation makes the synthesis of a pan-EVA71 protective vaccine more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it appears that a combination of host and viral factors is associated with the likelihood of progressing to severe disease. These factors include polymorphisms within host immune and receptor-associated genes ( 3 5 ). While there is some cross-reactivity among the different genogroups (A, B1 to B5, and C1 to C5) ( 6 ), the antigenic variation makes the synthesis of a pan-EVA71 protective vaccine more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…EV71 causes HFMD, neurological complications or even fatal diseases in young children and infants. It is still a major challenge due to some children experiencing serious consequences [ 28 ]. PRRs are the first line of defense against EV71 infection.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have noticed that genetic factors are significantly associated with the susceptibility and severity of HFMD. Li et al 12 demonstrated that patients with CD55 rs2564978 C allele or CC genotype were more susceptible to EV‐A71 infection and TC genotype carriers had a greater probability of developing severe HFMD. A study showed that rs11574129 AA genotype and rs739837 GG genotype of vitamin D receptor ( VDR ) gene could reduce the risk of severe EV‐A71‐associated HFMD in Chinese children, accompanied by low serum vitamin D levels 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 3 showed that the TLR7 rs3853839 C allele was a risk factor for EV‐A71‐associated HFMD and C allele carriers had lower levels of TLR7 mRNA, interferon‐α (IFN‐α), and interleukin‐6 (IL‐6), leading to defects in innate and humoral immunity, which might be related to the severity of HFMD. Meanwhile, Li et al 9 demonstrated that the single‐nucleotide polymorphism (SNP) rs3853839 was related to the susceptibility and severity of HFMD in Chinese male children. In the present study, we aimed to determine whether TLR3, TLR4, TLR7 and TLR8 gene polymorphisms were related to the severity of EV‐A71‐associated HFMD in a Chinese children population.…”
Section: Introductionmentioning
confidence: 99%